Effect of injection strategies on a single-fuel RCCI combustion fueled with isobutanol/isobutanol + DTBP blends. (15th October 2020) - Mohammadian, Amir; Chehrmonavari, Hamed; Kakaee, Amirhasan; Paykani, Amin
Highlights: Isobutanol/isobutanol + DTBP was used in a single-fuel RCCI concept. Effect of injection strategies on single-fuel RCCI concept was studied. The optimal injection timing and pressure, and spray cone angle were determined. Reduction in DI fuel ratio with improvements in GIE, and emissions were noticed. Abstract: In recent years, improved combustion controllability through in-cylinder reactivity stratification by using two different fuels have led to introduction of dual-fuel reactivity controlled compression ignition (RCCI) strategy. In conventional RCCI, gasoline or natural gas can be used as the low-reactivity fuel, and diesel or biodiesel can be used as the high-reactivity fuel. This strategy has the potential to operate with a single low-reactivity fuel and direct injection (DI) of the same fuel blended with a small amount of cetane improver. In the present study, numerical simulations have been carried out to study injection strategy in a single-fuel RCCI engine fueled with isobutanol – isobutanol + 20% di-tert-butyl peroxide (DTBP). Firstly, the effects of start of injection (SOI) timing, injection pressure (p inj ), spray cone angle (SCA), and DI fuel ratio were explored. Then, the effect of DI fuel ratio was discussed in each best case in order to decrease the high DI requirement. The results indicate that SOI = −88° ATDC, p inj = 1400 bar, and SCA = 45° can improve the single-fuel RCCI engine performance and emissions compared to the baseline case (SOI = −58° ATDC, p inj = 600 bar, SCA = 72.5°). Moreover, it is shown that by advancing the SOI timing to −88° ATDC, a 20% reduction in DI ratio, 3.3% increase in gross indicated efficiency (GIE) together with reductions in CO, and NO x emissions by 3.56 g/kW-h and 0.254 g/kW-h, could be achieved, respectively.